Association of Anaesthetists: anaesthesia and peri‐operative care for Jehovah's Witnesses and patients who refuse blood. (30th September 2018) - Klein, A. A.; Bailey, C. R.; Charlton, A.; Lawson, C.; Nimmo, A. F.; Payne, S.; Ruck Keene, A.; Shortland, R.; Smith, J.; Torella, F.; Wade, P.
Summary: There are approximately 8.5 million Jehovah's Witnesses and around 150, 000 live in Great Britain and Ireland. Based on their beliefs and core values, Jehovah's Witnesses refuse blood component transfusion (including red cells, plasma and platelets). They regard non‐consensual transfusion as a physical violation. Consent to treatment is at the heart of this guideline. Refusal of treatment by an adult with capacity is lawful. The reasons why a patient might refuse transfusion and the implications are examined. The processes and products that are deemed acceptable or unacceptable to Jehovah's Witnesses are described. When a team is faced with a patient who refuses transfusion, a thorough review of the clinical situation is advocated and all options for treatment should be explored. After discussion, a plan should then be made that is acceptable to the patient and appropriate consent obtained. When agreement cannot be reached between the doctor and the patient, referral for a second opinion should be considered. When the patient is a child, the same strategy should be used but on occasion the clinical team may have to obtain legal help.